AN ECONOMETRIC PERSPECTIVE ON PUBLIC ENVIRONMENTAL CAPITAL FORMATION AND INDUSTRIAL EMISSIONS: EVIDENCE FROM SEVEN EU COUNTRIES - GEORGE-CORNEL DUMITRESCU (Global Economic Observer)
This paper investigates the dynamics and relationship between greenhouse gas emissions from industrial processes and product use (GHG), and general government expenditures on environmental protection in gross fixed capital formation (GFCF). Based on data extracted from Eurostat covering the period from 2005 to 2022, we employed ordinary least squares regression models to assess the degree to which general government expenditures in environmental protection in gross fixed capital formation impact greenhouse gas emissions from industrial processes, and product use. The results show a negative and statistically significant relationship between GFCF and GHG in France, Germany and Romania and the assumptions of linear regression were met, or corrections were employed using the Prais-Winsten procedure. In contrast, there is no clear linear relationship between the indicators analysed in Bulgaria, the EU, Hungary and Poland. The results show that public expenditures on gross fixed capital formation in environmental protection have a heterogeneous effect on greenhouse gas emissions across the selected countries. Therefore, each country should tailor its strategies to mitigate emissions.